Implementasi Pendidikan Karakter Melalui Kegiatan SKI (Seksi Kerohanian Islam) Di Madrasah Aliyah Negeri Salatiga - Aprilyanti, Siti (Pascasarjana UIN Raden Mas Said Surakarta, 2021)
AbstractImplementation of character education through SKI activities (Islamic spirituality section) at Madrasah Aliyah, Salatiga State. The main problem is how to implement character education in SKI (Islamic Spirituality Section) activities at Madrasah Aliyah, Salatiga State.This research is a type of qualitative research using a descriptive approach. The subjects of this study were the Principal, Deputy Head of Student Affairs, BK Teachers, Spiritual Leaders, Rohis Leaders and Students. Collecting data using the method of observation, interviews, and documentation. Data analysis through data reduction, data presentation, and conclusions check the validity of the data through triangulation.The results of the study indicate that the State Islamic School of Salatiga has implemented character education in SKI (Islamic Spiritual Section) activities through habituation by applying character values, the following are the results of the researcher's analysis; The implementation of character education through SKI (Islamic Spirituality Section) activities at Madrasah Aliyah Negeri Salatiga is to apply character values including religious, discipline, responsibility, social care, environmental care, creativity, curiosity, friendly/communicative and culture of shame.Keywords: Implementation, Character Education, SKI Activities (Islamic Spiritual Section)